Analysis of the Influence of Product Quality, Service Quality and Distribution Channels on Customer Satisfaction at PT Suminsurya Mesindoleestari - Triyani Chaisar; Melinda Siregar; Wati Wati; Sri Puspa Dewi (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of this research is to analyze the influence of product quality, service quality and distribution channels on customer satisfaction at PT Suminsurya Machinedolestari. The research method used in this research is quantitative research. The sampling technique used simple random sampling and a sample size of 50 customers was obtained. The research results obtained from this research show that from the results of the t test, the tcount results for all variables are greater than ttable and the significance is smaller than 0.05, so it can be concluded that partially product quality has a significant effect on customer satisfaction, partially service quality has a significant effect on customer satisfaction and partially distribution channels have a significant effect on customer satisfaction. From the results of the F test, it was found that simultaneously the three customer satisfaction factors, namely product quality, service quality and distribution channels, had a significant effect on customer satisfaction with a Fcount value greater than Ftable (14.824 > 2.80) and a significance of 0.000 which was below 0. 05. From the results of the coefficient of determination test, it was found that 45.8% of the customer satisfaction variable was influenced by product quality, service quality and distribution channel variables, while the remaining 54.2% was explained by the influence of other factors or variables outside of the research such as price, brand image. , and others not discussed in this study.